基于伪刚体模型的柔顺簧片性能分析 - 强怀博 (Jixie chuandong)
The precision of micromanipulator is affected by the performance compliant spring.With consideration of nonlinearity and large deformation,the mechanics analysis model of compliant spring is built based on principle of Bernoulli-Euler equation and pseudo rigid body model is proposed.The relationships among property of load,displacement,curvature etc and geometrical parameter are studied and the mechanics equation is obtained.Finally,the validity of this model is verified by experiments.This research has reference value on design of precision micromanipulator.